I Borbone sul Palatino.: Documenti inediti sugli Orti Farnesiani dal 1731 al 1861 - Santoro, Valentina; Sielhorst, Barbara; Terzi, Lorenzo (Römische Mitteilungen, 2022)
This article presents the results of new discoveries from the State Archive of Naples about the 130 year long era when the Bourbons owned the Farnese Gardens on the Palatine hill. Contrary to the widely held belief that it was a time of neglect and inattention, and thanks to several hitherto unknown documents found in the archive, this almost ignored period has turned out to be full of events and projects that involved not only the administration of cultivations but even maintenance and restoration of Renaissance and ancient Roman buildings. Excavation and research to unearth antiquities from the Palaces of the Emperors was also undertaken.